Improved Production of Xylanase in Pichia pastoris and Its Application in Xylose Production From Xylan - Miao, Ting; Basit, Abdul; Liu, Junquan; Zheng, Fengzhen; Rahim, Kashif; Lou, Huiqiang; Jiang, Wei (Frontiers in Bioengineering and Biotechnology, 2021)
Xylanases with high specific activity has been focused with great interest as a useful enzyme in biomass utilization. In this research, the production of recombinant GH11 xylanase (MYCTH_56237) from Myceliophthora thermophila through the engineering of N-terminal signal peptide in P. pastoris has been improved. The production of newly recombinant xylanase (termed Mtxyn11C) was improved from 442.53 U/mL to 490.7 U/mL, through a replacement of α-factor signal peptide with the native xylanase signal peptide segment (MVSVKAVLLLGAAGTTLA) in P. pastoris. Scaling up of Mtxyn11C production in a 7.5 L fermentor was improved to the maximal production rate of 2503 U/mL. Moreover, the degradation efficiency of Mtxyn11C was further examined. The hydrolytic mode of action analyses towards the birchwood xylan (BWX) revealed that Mtxyn11C was clearly more effective than commercial xylanase and degrades xylan into xylooligosaccharides (xylobiose, xylotriose, xylotetraose). Significantly, Mtxyn11C in combination with a single multifunctional xylanolytic enzyme, improved the hydrolysis of BWX into single xylose by 40%. Altogether, this study provides effective strategies for improved production of xylanase together with rapid conversion of xylose from BWX, which provides sustainable, cost-effective and environmental friendly approaches to produce xylose/XOSs for biomass energy or biofuels production.